Analysis of Factors Affecting Employee Engagement - Antony Sentoso; Kelly Kelly (Program Studi Manajemen, Fakultas Ekonomi, Universitas Langlangbuana, 2021)
Batam City is a special city that has become a tourist spot with a great potential business opportunity. Therefore, it is necessary to have qualified facilities and services from hotel employees in increasing tourist visits to use their services. By improving the quality of employee services, companies can also reduce unnecessary expenses and remain competitive with other hotels. Therefore the company must provide more value to employees so that employees can provide similar feedback to the company. This study aims to determine the effect of job satisfaction, compensation, leadership, and work environment on employees' attachment to four-star hotels in Batam. The sampling method used was the purposive sampling method through google form and collected 213 valid questionnaires. This research was conducted as a quantitative study to explain the relationship between variables, then managed by the SPSS program. From the results of SPSS processing data, it can be seen that job satisfaction, leadership style, and work environment have a significant positive relationship with employee engagement, while compensation is not significant for employee engagement. Researchers hope that four-star hotel management can study this research to outperform employee engagement. Keywords: